FUNCTIONAL CAPACITY IN CHILDREN AND ADOLESCENTS WITH CONGENITAL HEART DISEASE - Schaan,Camila Wohlgemuth (2019)
ABSTRACT Objective: To evaluate the physical activity level and functional capacity of children and adolescents with congenital heart disease and to describe correlations between functionality, surgical and echocardiographic findings, metabolic and inflammatory profile and differences between acyanotic and cyanotic heart defects. Methods: A cross-sectional study including children and adolescents with congenital heart disease between six and 18 years old that were evaluated with the 6-minute walk test (6MWT) to assess functional capacity. The short version form of the International Physical Activity Questionnaire (IPAQ) was performed to evaluate physical activity levels. Also, echocardiography and blood collection, to evaluate the metabolic (blood glucose, lipids, insulin) and inflammatory markers (C-reactive protein), were assessed. Results: Twenty-five individuals were evaluated. Of them, 14 had acyanotic heart defects and 11 cyanotic heart defects. Mean age was 12.0±3.7 years, and 20 (80%) were male. IPAQ showed that six (24%) individuals were very active, eight (32%) were active, nine (36%) had irregular physical activity, and two (8%) were sedentary. The mean distance walked in the 6MWT, considering all studied individuals, was 464.7±100.4 m, which was 181.4±42.0 m less than the predicted (p=0.005). There was a positive correlation between Z score 6MWT and the number of surgical procedures (r=-0.455; p=0.022). Conclusions: Children and adolescents with congenital heart disease have low functional capacity, but they are not completely sedentary.